Sentence Analysis in Saussure's Structural Linguistics: Implications for Statements of Victims of the Kanjuruhan Tragedy - Sintia, Haqsirvenny; Anwar, Miftahulkhairah (Bahasa: Jurnal Keilmuan Pendidikan Bahasa dan Sastra Indonesia, 2023)
This article describes the syntagmatic and paradigmatic approaches to language. This is to distinguish two different approaches or perspectives on language because language units can explore syntagmatic and paradigmatic connections. The syntagmatic approach is contrasted with the paradigmatic approach approach to studying three different levels of analysis namely, phonology, morphology, and syntax, as a sub-discipline of linguistics. In other words, the subject matter for studying the two different approaches is mainly related to linguistic forms, phonemes (the study of sound changes at the level) structure of sounds, known as phonology), and morphemes (the study of words). structure at the level of internal word structure, known as morphology), and words (the study of how words combine to form grammatical sentences, known as syntax). This article also discusses the application of syntagmatic and paradigmatic in language teaching. AbstrakArtikel ini menjelaskan tentang pendekatan sintagmatik dan paradigmatik pada bahasa. Hal ini untuk membedakan dua pendekatan atau perspektif yang berbeda tentang bahasa karena unit bahasa dapat mengeksplorasi sintagmatik dan paradigmatik hubungan. Pendekatan sintagmatik dikontraskan dengan paradigmatik pendekatan untuk mempelajari tiga tingkat analisis yang berbeda yaitu, fonologi, morfologi, dan sintaksis, sebagai sub-disiplin ilmu linguistik. Dengan kata lain, pokok bahasan untuk mempelajari dua pendekatan yang berbeda terutama berkaitan dengan bentuk linguistik, fonem (studi tentang perubahan suara pada tingkat struktur suara, yang dikenal sebagai fonologi), morfem (studi tentang kata). struktur pada tingkat struktur kata internal, yang dikenal sebagai morfologi), dan kata (studi tentang bagaimana kata-kata bergabung untuk membentuk kalimat gramatikal, dikenal sebagai sintaksis). Artikel ini juga membahas penerapan sintagmatik dan paradigmatik dalam pengajaran bahasa.